PRODUCTION OF BIODIESEL FROM COOKING OIL USING IMOBILIZIED LIPASE ITB1.1 AS CATALYST - Alfa Ni'am Putri, Salwa
Lipase (EC 3.1.1.3) is one of the hydrolase enzymes that is widely used in industrial fields such as food industry, medicine, detergents, biodiesel etc. therefore the production of lipase in large quantities is needed. However, the application of the enzyme in industry faced obstacles due to its relatively expensive price and its reduced activity at high temperature. Lipase ITB1.1 is a thermostable enzyme that can remain its activity up to 80 oC and can be used as a catalyst in the transesterification reaction for biodiesel production. In previous studies, lipase ITB1.1 has been successfully expressed in Escherichia coli. In this study the plasmid pPICZ?A which has a gene encoding lipase ITB1.1 was transformed into P. pastoris GSS15. Then Lipase ITB1.1 was purified by Ni-NTA affinity chromatography, immobilized, and used as a catalyst in biodiesel production. Recombinant lipase was produced at 30 oC with a shaking speed of 180 rpm and induced with the optimum methanol concentration of 2% for 6 days. The hydrolysis activity test was carried out at pH 8 and 70 oC for 15 minutes using pNPD (4-nitrophenyl decanoate) as substrate. The specific activity of pure lipase (8,1712 ± 0,07 U/mg) increased 24 times compared to the crude extract (0,3373 ± 0,03 U/mg). Immobilization of lipase ITB1.1 was carried out by combining the Bioimprinting method with Cross Linked Protein Coated Microcrystals (IMCLPCMC). Each immobilization step was proven to be able to increase the performance of the enzyme based on the conversion percentage of the transesterification reaction, the Bioimprinting method produced 6.88%, the Bioimprinting Protein Coated Microcrystals (IM-PCMC) method produced 12.15% and IM-CLPCMC produced 17. 6% conversion. The immobilized enzyme was able to maintain 85% of initial activity after nine cycles and remain 91% of its activity after stored at 4 oC for 20 days. The free and immobilizied lipase could reach 17,8% and 17,6% transesterification conversion. Free and immobilized lipase ITB1.1 was used as a catalyst in the transesterification reaction for biodiesel production. Biodiesel with a ratio of cooking oil to methanol of 1:6 produces methyl ester 2.25 times greater than the ratio of 1:4. Characterization of biodiesel using GC-MS showed the formation of 82.8% methyl palmitate for the free enzyme and 82.2% for the immobilized enzyme. The type of solvent affected the activity of the free lipase ITB1.1 in catalyzing biodiesel production. There was a decrease in activity when the solvent was changed from tbutanol to n-hexane. However, this effect was not observed for immobilized enzymes. The immobilized enzyme activity was not too different in the use of the two solvents.